Studying the Effect of Plant Growth Regulators Ivin, Methyur and Kamethur on Growth and Productivity of Sunflower - V. A., Tsygankova; I. V., Voloshchuk; V. M., Kopich; S. G., Pilyo; S. V., Klyuchko; V. S., Brovarets (JOURNAL OF ADVANCES IN AGRICULTURE, 2023)
In field conditions, the effect of plant growth regulators Ivin (N-oxide-2,6-dimethylpyridine), Methyur (sodium salt of 6-methyl-2-mercapto-4-hydroxypyrimidine), Kamethur (potassium salt of 6-methyl-2-mercapto-4-hydroxypyrimidine) on growth and productivity of sunflower (Helianthus annuus L.) variety Bastion was studied. The growth-regulating activity of plant growth regulators Ivin, Methyur and Kamethur was compared with the growth-regulating activity of the auxin IAA (1H-Indol-3-yl)acetic acid). It was found that the treatment of seeds before planting in the soil with water solutions of Ivin, Methyur and Kamethur, used at a concentration of 10-7M, contributes to an increase in morphological parameters (length of shoot and root, fresh weight of plant and basket) and biochemical parameters (content of chlorophylls a and b, and carotenoids) of sunflower (Helianthus annuus L.) variety Bastion grown in field conditions for 3 months. The growth-regulating activity of plant growth regulators Ivin, Methyur and Kamethur was higher than the growth-regulating activity of the auxin IAA used at the same concentration of 10-7M. The obtained results confirmed the possibility of using plant growth regulators Ivin, Methyur and Kamethur to increase the length of shoot and root, fresh weight of the plant and basket, and the content of chlorophylls in sunflower (Helianthus annuus L.) variety Bastion.